Condition Monitoring of Distribution Transformer Using Internet of Things (IoT) - Khule, S.S. (Journal of Advanced Research in Signal Processing and Applications, 2021)
Transformers are utilized for electricity distribution and transmission which decreases the main voltage to the use voltage for customer. As distribution transformers are very higher in electrical manufacturing consequently this article offerings the system which monitor dissimilar parameters of distribution transformer. There are double units which are remote terminal unit (RTU) and monitoring unit. Remote terminal unit contain of examining parameters such as current, temperature, rise and fall in oil level, vibration and humidity with the assistance of PIC 18F4550. All monitoring limitations are handled and if any irregularity happens, the system sends Alert communications to the mobile phones and recorded in system memory finished (ADC) analog to digital converter. All parameters values are sent to monitoring node through GPRS. If any emergency condition occurs immediately message send to the consistent engineer through GSM and likewise on webpage we can get alert about it finished GPRS. Near remote terminal unit buzzer will beep and LCD stretches announcement about emergency condition. An engineer at transformer cannot uninterruptedly keep an eye on transformer therefore given planned system does communication with us at emergency conditions of distribution transformer finished GSM/ GPRS module. How to cite this article: Parihar AR, Khule SS. Condition Monitoring of Distribution Transformer using Internet of Things (IoT). J Adv Res Sig Proc Appl 2019; 1(2): 9-13.